Assn., n. (Oxford English Dictionary, 2023)
BACKGROUND: Patient-reported experience measures (PREMs) and patient-reported outcome measures (PROMs) are increasingly recognized as valuable tools for evaluating healthcare quality. This study aims to explore nurses' perceptions across diverse clinical settings regarding the usefulness of PREMs and PROMs for identifying opportunities to improve care and informing quality improvement initiatives. MATERIALS AND METHODS: Interpretive, exploratory, multicenter qualitative study conducted between November 2025 and February 2026. Five focus groups were held with 32 nurses recruited through purposive sampling from inpatient wards, adult and neonatal intensive care units, emergency departments, operating rooms, and oncology units across four HM hospitals in Madrid. Data were collected using a semi-structured interview guide and analyzed through inductive thematic analysis. RESULTS: Six themes emerged: 1) communication, therapeutic relationship, and humanized care as key determinants of patient experience; 2) holistic care, particularly comfort, patient safety, and pain management; 3) clinical information and patient education to reduce uncertainty and improve continuity of care; 4) positive perceptions of PREMs and PROMs despite their limited systematic implementation; 5) organizational constraints, workload, and time pressure as major barriers; and 6) opportunities for innovation through humanization strategies, technology integration, and advanced nursing practice. CONCLUSIONS: Nurses perceive PREMs and PROMs as valuable resources for improving patient-centered case and supporting quality improvement. However, their integration into routine clinical practice remains limited by organizational and structural barriers. Addressing these challenges may facilitate the systematic use of patient-reported measures to enhance care quality and patient outcomes.